Chlorhexidine gluconate lavage during total joint arthroplasty may improve wound healing compared to dilute betadine - Brandon E. Lung; Ryan Le; Kylie Callan; Maddison McLellan; Leo Issagholian; Justin Yi; William C. McMaster; Steven Yang; David H. So (Journal of Experimental Orthopaedics)
Abstract Purpose Intraoperative wound irrigation prior to closure during total joint arthroplasty (TJA) is an essential component of preventing infections and limiting health care system costs. While studies have shown the efficacy of dilute betadine in reducing infection risk, there remains concerns over its safety profile and theoretical inactivation by blood and serum. This study aims to compare infection and wound complications between chlorhexidine gluconate (CHG) and betadine lavage during TJA. Methods All primary TJA between 2019–2021 were analyzed at a single institution, and periprosthetic joint infection (PJI), wound drainage, 30 and 90‐day emergency room (ER) readmission due to wound complications, aseptic loosening, and revision surgery rate were compared between patients undergoing intraoperative CHG versus betadine lavage prior to closure. Baseline demographics were controlled, and multivariate logistic regression was performed to compare complication rates. Results A total of 410 TJA, including 160 hip and 250 knee arthroplasties were included. Compared to the dilute betadine cohort, all TJA patients undergoing CHG lavage had a statistically significant lower 30 and 90‐day emergency room readmission rate due to wound complications. Both hip and knee arthroplasty patients with CHG had a statistically significant lower rate of postoperative superficial drainage and dressing saturation at clinic follow‐up, but only knee arthroplasty patients had significant decreased readmission rate for incisional wound vacuum placement and close inpatient monitoring of wound healing. Among all TJA, there was no significant association in the rate of PJI requiring return to the OR between groups. Conclusions Although betadine is cost‐effective and has been shown to reduce PJI rates, there remains concerns in the literature over soft tissue toxicity and wound healing. This study suggests CHG may be as efficacious as dilute betadine in preventing PJI while also decreasing the risk of superficial drainage and wound complications needing unplanned ER visits during the acute postoperative period.